A Mixed Integer Linear Programming Approach to Production Optimization in a Surface Treatment Area of the Aerospace Industry - Luche, José Roberto Dale; Freitas, Claudia Regina de; Schmidt, Paulo Alberto Misfeldt; Marins, Fernando Augusto Silva; Silva, Aneirson Francisco da (Yugoslav Journal of Operations Research; Online firstDO - 10.2298/YJOR250524033L, 2025)
Production scheduling, especially in intricate sectors like aerospace, is essential. This study presents a Mixed Integer Linear Programming (MILP) model to optimize production in the surface treatment area of an aerospace company. The complex task involves several constraints, including raw material alloy type, tank capacity, and fixture design for parts. The goal is to find the optimal combination to maximize production, efficiency, and safety. Unique to this problem is the integration of factors such as different tanks, fixtures, scheduling, and geometric constraints. Technical requirements have been integrated as constraints to satisfy aircraft manufacturing certifications. Experiments with thirty real and thirty simulated scenarios showed that the proposed model significantly outperformed the company's existing methods. In the best case, it demonstrated the potential to more than double the production with the same resources. The results underscore the existing capacity to take on new products and clients, highlighting the potential for increased efficiency. Spatial optimization allows for processing more parts per cycle, thus reducing time, costs, and environmental impact. This study adds value to optimization literature, offering a novel approach to a real and multifaceted problem in the surface treatment industry, with applications extending to other industrial contexts where spatial optimization and efficient scheduling are key.